Examine the need for retraining and advanced training - Kulakova, Natalya; Sadykova, Jeanne (Рroblems of engineering and professional education, 2023)
The article deals with the study of the need for retraining and advanced training of specialists in the field of occupational safety and identify optimal training programs.